ECONOMIC EVALUATION OF THE EFFECTIVENESS OF LOW MOLECULAR WEIGHT HEPARIN AND INTERMITTENT PNEUMATIC COMPRESSION IN WOMEN IN A CYCLE OF IN VITRO FERTILIZATION - A. P. Momot; I. V. Molchanova; N. A. Semenova; O. P. Tomilina; E. A. Elykomov; O. G. Borisova (Фармакоэкономика)
To solve the problem of infertility in the world assisted reproductive technologies (ART) are widely used, which relate to the financial and expensive high-tech medical care. This paper shows that the conduction of therapeutic correction of excessive thrombin generation and / or hypofibrinolysis in patients in a cycle of in vitro fertilization (IVF) is economically more justified than the standard management of patients by reducing recurrent IVF.